EXTERNAL FACTORS OF JUVENILE DELINQUENCY AMONG STUDENTS IN THE AREA OF TRADITIONAL NIGHT CLUB - Niken Agus Tianingrum; Sri Sunarti (Jurnal Ilmu Kesehatan, 2020)
Nowadays, world is challenged a condition in which case the number of adolescent are bigger than before, but, this group of age are also facing the health and social problem such juvenile delinquency. External factors became the trigger factor of them, such as peer’s influence and environment. This study aims to estimate the prevalence of juvenile delinquency and clearly identify external factors toward juvenile delinquency among students who live in the area of traditional night club. A cross sectional study was conducted among 369 students aged 11 to 16 years old. A total sampling was drawn from 2 Junior High Schools near Traditional Night Club in Samarinda. Data were collected using a validated questionnaire in Bahasa Indonesia. Variables measured include socio-demographic criteria, peers’ and environmental influence and juvenile delinquency. Data was analyzed trough descriptive statistic and multiple linier regression.Results indicated that the prevalence of juvenile delinquency among student ages 11-16 years was high (69.7%). This study showed that peers influence and environment contribute to juvenile delinquency. Simultaneously, peers and environment also influence juvenile delinquency (p-value<0.0001). The result suggested the existence of school-based program for healthy adolescent as a ways to provide a better information and health community in school.